Analyzing the Interaction of Andrographolide and Neoandrographolide, Diterpenoid Compounds From Andrographis Paniculata (Burm.F) Nees, to Cyclooxygenase-2 Enzyme by Docking Simulation - Jutti Levita; Enade P. Istyastono; As'ari Nawawi; Abdul Mutholib; Iwan J. P. de Esch; Slamet Ibrahim (Journal of Mathematical and Fundamental Sciences, 2009)
Cyclooxygenase (COX), an enzyme involved in the conversion of arachidonic acid to prostaglandins, exists in two isoforms, which are COX-1 and COX-2. Despite the similarities of COX-1 and COX-2, the two isoforms show subtle differences in amino acid composition at the active sites. Since COX-1 has isoleucine, a bulkier amino acid at position 523 than COX-2's valine, it allows COX-2 to have a larger space in its active site. Andrographolide reduces COX-2 expression induced by PAF and fMLP in HL60/neutrophils. Neoandrographolide inhibits COX-2 expression at the translational level. The purpose of this study is to examine the binding modes of andrographolide and neoandrographolide against COX-1 and COX-2 in terms of hydrogen bonds and docking energy, to understand their antiinflammatory property. The docking simulation indicates that both andrographolide and neoandrographolide are able to be located in the COX-2's binding pocket but not in the COX-1's. It confirms that COX-1's binding pocket is smaller than COX-2's. Based on this study, both andrographolide and neoandrographolide show selective inhibitory property to COX-2. Their selectivity are due to their specific interaction with Arg 513 in the binding pocket of COX-2, which is also shown by SC-558, a COX-2 selective inhibitor.